2023
DOI: 10.3390/foods12163009
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Nitrogen Fertilizer Change the Quality of Waxy and Non-Waxy Broomcorn Millet (Panicum miliaceum L.) Starch

Abstract: The overuse of nitrogen fertilizers has led to environmental pollution, which has prompted the widespread adoption of biochar as a soil conditioner in agricultural production. To date, there has been a lack of research on the effects of biochar and its combination with nitrogen fertilizer on the quality of broomcorn millet (Panicum miliaceum L.) starch. Thus, this study examined the physicochemical characteristics of starch in two types of broomcorn millet (waxy and non-waxy) under four different conditions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The HansePlant, Agroflorin, and Bioecohum treatments resulted in significantly elevated starch contents compared with control maize samples, with values of 3.97%, 5.61%, and 5.67%, respectively. Previous research reported that N fertilizer application substantially increased maize starch [46].…”
Section: Effects Of Different Fertilizers On Maize and Soybean Qualitymentioning
confidence: 93%
“…The HansePlant, Agroflorin, and Bioecohum treatments resulted in significantly elevated starch contents compared with control maize samples, with values of 3.97%, 5.61%, and 5.67%, respectively. Previous research reported that N fertilizer application substantially increased maize starch [46].…”
Section: Effects Of Different Fertilizers On Maize and Soybean Qualitymentioning
confidence: 93%